Bahasa Santun melalui Kalimat "Tolong, Maaf dan Terimakasih" di Taman Kanak-Kanak Islam Terpadu Cendekia, Takengon, Aceh Tengah: INDONESIA - Bakrie, Suminah (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2023)
Takengon Scholar Integrated Islamic Kindergarten is one of the educational institutions located in the Central Region of Aceh. What's interesting about TK IT Scholar is that in effective communication, school members, especially teachers, use TMT sentences (Please, Sorry, and Thank You) which will have an impact on children's Polite Language. The purpose of this study is to find out how the concept of polite language is applied in the Central Aceh Takengon IT Cendekia Kindergarten, especially in using the TMT sentence (Please, Sorry, and Thank you). This research method is a qualitative research that is, in the process of obtaining data in accordance with the objectives or research problems. What is needed is information that is as complete as possible or as deep as possible regarding the symptoms that exist within the scope of the research object. The approach used in this study is a descriptive approach as well as educational science which refers to educational theories. The results achieved descriptively are the use of polite language with TMT sentences (Please, Sorry, and Thank You) with the concept of building effective communication, being a good listener, understanding children's feelings and giving positive praise packed with habituation activities such as Morning Journal, Activities centers, rest activities and closing activities.